2008
DOI: 10.1111/j.1530-9134.2008.00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Patents, Research Exemption, and the Incentive for Sequential Innovation

Abstract: We develop a quality ladder model to study the R&D incentive impacts of intellectual property rights with a "research exemption" or "experimental use" provision. The innovation process is sequential and cumulative and takes place alongside production in an infinite-horizon setting. We solve the model under two distinct intellectual property regimes, characterize the properties of the relevant Markov perfect equilibria, and investigate the profit and welfare effects of the research exemption. We find that firms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…Our results were in agreement with the discussion provided in Pardey et al (2013) and with theoretical results derived in Moschini and Yerokhin (2008). Each of the two primary IPP systems has been shown to have advantages and disadvantages, and neither of them is better than the other under all possible circumstances.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results were in agreement with the discussion provided in Pardey et al (2013) and with theoretical results derived in Moschini and Yerokhin (2008). Each of the two primary IPP systems has been shown to have advantages and disadvantages, and neither of them is better than the other under all possible circumstances.…”
Section: Discussionsupporting
confidence: 92%
“…International Seed Federation data showed higher sustained wheat yields for countries where private sector wheat breeding is a competitive business (France, Germany, United Kingdom) compared with countries where wheat breeding remains largely in the public domain (Argentina, Australia, Uruguay, United States). Moschini and Yerokhin (2008) showed that when research was risky or expensive, then an IPP system with a research and commercialization exception would undermine incentives to undertake that type of research. Kolady et al (2012) showed that yield trends in India for maize (Zea mays L.) and pearl millet [Pennisetum glaucum (L.) R.…”
Section: Previous Economics Based Analyses Of Intellectual Property Pmentioning
confidence: 99%
“…Studies on the implications of patenting in the context of sequential innovation typically assume that the timing of the second, infringing innovation is exogenous, and occurs either immediately after the first innovation (Chang, 1995; Green and Scotchmer, 1995; Chou and Haller, 2007), or after the expiration of the first patent (Horowitz and Lai, 1996; Denicolo, 2000; Moschini and Yerokhin, 2008). The effect of patent life or scope on a second innovator who does not infringe the first patent is considered in a distinct set of studies, including Gallini (1992), O'Donoghue (1998), and Hopenhayn and Mitchell (2001).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to understand that the foregoing empirical studies address a narrow question: given that the initial innovation has happened, do IPRs (e.g., patents) on this innovation favor or hinder This question is addressed, in the context of plant-related IPRs, by Moschini and Yerokhin (2008).…”
Section: Iprs and Cumulative Innovationmentioning
confidence: 99%